THE MOTIVATION AND ITS IMPORTANCE AS A VEHICLE IN THE TEACHING OF THE MATH - Viale Tudela, Hector Ernesto (2012)
Motivation is a methodological vehicle that must necessarily be implemented in the triad system called teaching-learning-university development. This, the motivation, cannot be reduced to some minutes at the beginning of the classes or to the development of a particular topic. Neither focuses on capturing the attention of students for a few minutes. The process of motivation is much more complex and starts from the conception of the course and then the design of the same. The motivation is not only directed at the cognition of the students. It has, rather, a high emotional component, as well as a great relationship with the role of the teacher, both within and outside the classroom. This is why the role of the teacher of these times should focus mainly on "induce and cause grounds in their students". That is to say, to motivate them.